Groundwater utilization and its environmental sustainability in coastal aquifers of Dakshina Kannada District, Karnataka, India - M C Jayaprakash; Ekaputra Rinaldi; Channabasappa K. (E3S Web of Conferences)
Water is one among the foremost precious of natural resources. In many regions of the world, the pressures of economic development are creating a surface water scarcity. Study of groundwater sustainability– like to remind people that most of the world’s available freshwater is stored underground. The best institutional set up for any country depends on its system of government, its climatic and hydrological context and its social and economic circumstances. Groundwater resources to meet current and future beneficial uses without causing unacceptable environmental or socioeconomic consequences. The methods that promote the wise use of groundwater supplies, is need to determine strategies that promote groundwater sustainability. Groundwater users have not generally had to pay anything like “full economic cost” for groundwater use, nor have groundwater polluters had to pay for clean-up of their contamination. Thus, this study aims to determine the strategies that promote ground-water sustainability and groundwater resources to meet present and future beneficial uses without causing un-desirable environmental or socioeconomic consequences.